Guerre et diplomatie Lettres d'Iluni roi d'Enunna d'une collection privée - Guichard, Michaël 1971- (2016)
The reign of Iluni king of Enunna, who was contemporary of Samsu-iluna, can be a little better known thanks to five new letters coming from a Parisian collection. Having reigned at least 6 years, he entered into diplomatic relationships with several sovereigns East of Mesopotamia, in particular with the kingdom of Kakmûm and especially that of Niqqum. A short-term correspondence is also proved true with Samsu-iluna, with whom, however, Iluni eventually entered war as is well known. The absence of any reference to the South of Babylonia in the letters of Iluni may suggest that his war and defeat in the face of Babylon happened several years after the revolt of Larsa by Rīm-Sîn II. One of the disputes between Enunna and Babylon was the trade of people captured by the Suteans. But since Samsu-iluna showed willingness in this respect, the war must have another cause not visible in our documents. It is possible that he saw in the development of Enunna under the reign of Iluni, an old ennemy of his country, and in the diplomatic efforts of Iluni to constitute a big alliance around him, an extreme danger for the safety of Babylon.